Ethnobotany of MandailingTribe in Batang Gadis National Park - Aswarina Nasution; Tatik Chikmawati; Eko Baroto Walujo; Ervizal Amir Muhammad Zuhud (Journal of Tropical Life Science, 2018)
Batang Gadis National Park (BGNP) located in Bukit Barisan Mountains, Sumatera Utara. A Mandailing tribe  who lives around the BGNP, has the unique local knowledge, such as processing young stem of rattan (Calamus manan) into pakkat (traditional food) and use rimbang (Solanum torvum) to neutralize toxins. These local knowledge could be lost because it only inherited orally from generation to generation. This study was aimed to reveal ethnobotany knowledge of Mandailing Tribe. The study was conducted in November 2015 in four villages around the BGNP, Sibanggor Jae, Hutabaringin Julu, Pastap Jae, and Botung Villages. Data were collected by interviewing informants in each village as well as the field survey through two approaches, emic and etic. A total of 262 plant species is used by Mandailing Tribe for subsistence and commercial needs. The highest utilization is for food  (106 species), followed by traditional medicines (81 species), firewood (29 species), building materials (35 species), and animal feed (25 species). People also used plant for household appliances, agricultural equipment, art materials, ropes and wrap, and pest control materials. Eme/rice (Oryza sativa) have the highest Index of Cultural Significance (ICS) values. The existence of this species is maintained for its local wisdom. Thus, involvement of  local  community will give great contribution to manage and conserve the BGNP area.